Efeitos de terapia por contensão induzida modificada na funcionalidade e no desempenho ocupacional pós-AVC : estudo randomizado controlado - Garcia, Rafael Eras (Universidade Federal de São Carlos, 2018)
Introduction: The Constraint Induced Movement Therapy (CIMT) is a family of treatment techniques with a behavioral approach derived from basic neuroscience, that aims to increase and improve the utilization of the affected upper limb of individuals with asymmetric use of it in their activities of daily living. The 3 hours a day protocol (10 days) requires a long period of attention from the therapist, raising the costs for rehabilitation institutions, decreasing the supply of care to be performed. Objectives: Compare the effects of modified CIMT (CIMT1h30) in relation to the protocol of CIMT3h and Control Group, on the functionality and occupational performance of hemiparetic subjects after stroke; evaluate the effects of the protocols of CIMT1h30, CIMT3h and Control Group on the quantity and quality of use of the paretic upper limb, from the participant's perception; evaluate the motor performance of the paretic upper limb and occupational performance; compare the influence of the behavioral package (CIMT1h30 X Control Group) in the results. Methodology: Single blinded randomized controlled trial, in which 30 participants were divided into three groups: (1) CIMT1h30: three sessions per week for four weeks, with an hour and a half duration each session; (2) CIMT3h: five sessions per week, for two weeks, with three hours duration each session; (3) Control Group: three sessions per week, for four weeks, with 40 minutes duration each session. The outcome measures used were: Motor Activity Log (MAL) and its two sub scales of movement quantity and movement quality; Wolf Motor Functional Test (WMFT); Canadian Occupational Performance Measure (COPM), and Saehan Hydraulic Hand Dynamometer and Saehan Hydraulic Pinch Gauge tests. Participants were evaluated in the pre- and post-treatment, as well as in the 6-month follow-up. The data were analyzed by the Tukey test for multiple comparisons (within-subject and between-group) and descriptive statistical analysis. Results: in relation to MAL and its two sub-scales, the participants of CIMT1h30 and CIMT3h presented significant improvement in the post-treatment, with maintenance of the results after 6 months (p <0.001), being the results superior to the Control Group. Regarding COPM, both for performance and satisfaction, the participants of CIMT1h30 and CIMT3h showed significant improvement in post-treatment, with maintenance of the results after 6 months (p <0.001); only the CIMT3h group presented statistical difference in relation to the Control for satisfaction. Analyzing the WMFT results in relation to time, the three groups showed a significant reduction in the time of test execution in the post-treatment (p <0.05), however, in the 6-month follow-up, only the CIMT1h30 and CIMT3h groups maintained the results. It was not possible to identify statistical difference between groups. When the quality of movement was analyzed through WMFT, the participants of the three groups showed significant improvement in the post-treatment (p <0.01), with maintenance of the results after 6 months only in the CIMT3h group, while in the between-group analysis the CIMT3h group was superior to Control. In relation to strength tests, only the CIMT3h group showed significant improvement in the 6-month follow-up (p <0.008) on the Pinch Gauge, but there was no difference in the between-group analysis. In relation to the Hand Grip, it was possible to identify significant improvement in the post-treatment in the CIMT1h30 and CIMT3h groups (p <0.02), but in the follow-up only for the CIMT3h group (p <0.001); in the between-group analysis there was no statistical difference between the three groups. Conclusion: The results of the study indicate that the CIMT1h30 protocol demonstrates potential to increase the use of the paretic upper limb of persons with motor sequelae due to a stroke, as well as in the perception of movement quality and occupational performance, with similar results as CIMT3h and higher than the control group.
Effects of modified constraint-induced movement therapy on post-stroke functional and occupational performance : randomized controlled trial
Keywords: Acidente vascular cerebral; Terapia por contensão induzida; Terapia ocupacional; Membro superior; Reabilitação neurológica; Constraint-induced movement therapy; Occupational therapy; Neurological rehabilitation; Stroke; Upper limb; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL